Simmons Longitudinal Study: Adaptation and Development Across the Lifespan (New England, United States), Grade 12 Data, Wave 5, 1990 - Reinherz, Helen Z. ([Verlag nicht ermittelbar], 2009)
The Simmons Longitudinal Study (SLS) is a community-based study that has prospectively traced the life course of a single-aged cohort from childhood (age 5) to adulthood (age 26). Data were collected from multiple informants at seven major time points: age 5 (1977), age 6 (1978), age 9 (1980-1981), age 15 (1987), age 18 (1990), age 21 (1993-1994), and age 26 (1998). Since its inception in 1977, the SLS has utilized a multidisciplinary, multimethod approach, with the dual goals of: (1) tracing the development and course of academic difficulties, behavior problems, and psychopathology; and (2) identifying factors that promote health functioning from early childhood (age 5) to adulthood (age 26). The SLS has consistently emphasized the identification of modifiable social and environmental risk and protective factors that can be targeted directly in prevention and intervention programs. To date, SLS has published 50 journal articles and 9 book chapters. The original study group was comprised of every child who entered kindergarten in the fall of 1977 in one public school district in a northeastern town in the United States. For this wave of the study, Wave 5, researchers revisited with study participants in 1990 when they were 18 years old and most were seniors in high school thinking about future plans for work and education. The interviews gathered information on future goals, behavioral and emotional adjustment, current social and interpersonal functioning, and mental health problems such as depression, and substance abuse and dependence.